Optimalisasi Pemanfaatan Sewa Barang Milik Negara di Politeknik Negeri Bandung - Maulanii, Nishrina Zukhrufi; Nugraha, Darya Setia; Putra, Sugih Sutrisno (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This study aims to find out the implementation of the utilization of state property leases at the Bandung State Polytechnic based on Minister of Finance Regulation Number 115/PMK.06/2020 concerning Utilization of State Property as well as the constraints and optimization efforts being made. This study used descriptive qualitative method. Data collection is done by interviews and documentation. The data analysis technique used is a qualitative descriptive analysis technique. The results of this study indicate that the implementation of leasing State Property at the Bandung State Polytechnic is in accordance with the provisions contained in the Minister of Finance Regulation Number 115/PMK.06/2020 concerning Utilization of State Property but cannot be said to be optimal, as evidenced by the lack of supporting facilities for activities rent and existing human resources are inadequate so that supervision and monitoring of the leased property does not run effectively and efficiently.